REPRESENTASI DIRI IBU DI TELEVISI (Analisis Semiotik Peirce dalam Program Talk show “Indonesia Lawyers Club” TVONE) - Maruli Bonardo Tua (Universitas Kristen Satya Wacana, 2015)
Television is one of the mass media which represents the reality of people's lives. Television can illustrate various dimensions of life in society including the representation of a mother. On the impressions that a mother is portrayed as a rough figure, ruthless and dares to kill his son. The mother is also represented as a figure who is able to understand the needs and wishes of children. Television was able to bring the reality of life in various aspects and has a role for imaging to reality around us. Imaging reality of the figure of the mother in the ILC TVONE footage is in the form of sound and image. With the analysis of semiotik Peirce was chosen because investigators wanted to reveal how the depiction of the figure of the mother in the impressions. From the results of the analysis can be put forward that in the impressions it is represented as the mother figure, a rugged, ruthless and dares to kill her child, the mother figure in the impressions it contrary to representations of the mother in a society that is very fond of his son figure, full of warmth and hospitality, are able to understand the needs and wishes of children.Key words: representations, mother, television, semiotics